2019
DOI: 10.3389/fpsyg.2019.01867
|View full text |Cite
|
Sign up to set email alerts
|

Do Self-Objectified Women Believe Themselves to Be Free? Sexual Objectification and Belief in Personal Free Will

Abstract: The present study aims to investigate the indirect link between sexual objectification and belief in personal free will. We hypothesized that being subjected to objectifying commentary would lead women to self-objectify and, in turn, to perceive themselves as having less personal free will. In this study, 105 women were asked to sign up a website created for this study by providing a personal description and a photo. After signing up, they received feedback from a fictitious male user. Depending on the conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Some studies have indeed shown that self-objectified women perceive themselves as powerless and as lacking the means to make autonomous decisions (Yang et al 2015), that is, they perceive themselves as less than human. In a similar vein, Baldissarri et al (2019) have recently found that compared to participants in non-objectifying and control conditions, after receiving comments focusing on their physical appearance women self-attributed fewer human mental states and lower free will as well as perceived themselves more as being an instrument rather than as a human being. Furthermore, after recollecting instances of sexual objectification, female participants rated themselves as less warm, competent, and moral as well as lacking in human nature and human uniqueness (Loughnan et al 2017; see also Chen et al 2013).…”
Section: Sexually Objectifying Media → Dehumanizationmentioning
confidence: 79%
“…Some studies have indeed shown that self-objectified women perceive themselves as powerless and as lacking the means to make autonomous decisions (Yang et al 2015), that is, they perceive themselves as less than human. In a similar vein, Baldissarri et al (2019) have recently found that compared to participants in non-objectifying and control conditions, after receiving comments focusing on their physical appearance women self-attributed fewer human mental states and lower free will as well as perceived themselves more as being an instrument rather than as a human being. Furthermore, after recollecting instances of sexual objectification, female participants rated themselves as less warm, competent, and moral as well as lacking in human nature and human uniqueness (Loughnan et al 2017; see also Chen et al 2013).…”
Section: Sexually Objectifying Media → Dehumanizationmentioning
confidence: 79%
“…However, manifestations of self‐objectification are not limited to the intrapersonal domain but also influence interpersonal behaviours (e.g., Saguy, Quinn, Dovidio, & Pratto, 2010). For example, self‐objectification is associated with less free will in women (Baldissarri et al, 2019) and less communication of their desires and needs (Sáez, Riemer, Brock, & Gervais, 2020), which may be particularly relevant in the domain of romantic relationships. Thus, future work should consider further correlates of self‐objectification to provide a better understanding of the sexual objectification process in romantic relationships.…”
Section: Discussionmentioning
confidence: 99%
“…However, manifestations of self-objectification are not limited to the intrapersonal domain but also influence interpersonal behaviours (e.g., Saguy, Quinn, Dovidio, & Pratto, 2010). For example, self-objectification is associated with less free will in women (Baldissarri et al, 2019) and less communication of their desires and needs , which may be particularly relevant in the domain of romantic relationships.…”
Section: Limitationsmentioning
confidence: 99%
“…When this happens indirectly, it will involve the internalization of women's experience of objectification, which then turns into self-objectification [9]. Self-objectification makes women see themselves only as a body and not as whole human beings [16].…”
Section: Subjectification and Objectificationmentioning
confidence: 99%